Personality traits of young people having a profile on a social networking site - Pawłowska, Beata; Potembska, Emilia; Świerczyńska, Justyna; Hrabowska, Olha (Polish Journal of Public Health, 2019)
Introduction. Social networking sites are virtual online communities, where users can design personal profiles available for public assessment, interact with friends, and meet with others, based on shared interests. SNS (social networking sites) have been defined as a “global consumer phenomenon” because they have been experiencing a sharp increase in popularity and use over the last decade. SNS websites, such as Facebook, are becoming increasingly popular, however, little is known about psychosocial variables, which are risk factors for excessive use of these websites. Aim. The aim of the work was to characterize personality traits (self-image characteristics, ways of coping with stress and aggression intensity) of youth who have a profile on a social networking site. Material and methods. The study included a total of 590 individuals from 16 to 18 years of age. Among the subjects, a group of 51 people without a profile was identified and 539 – with a profile on a social networking site. The group of teenagers was examined by means of statistical methods: a socio-demographic survey by the authors’ own design, H. G. Gough and A. B. Heilbrun’s Adjective Check List (ACL), Stress Coping Questionnaire (SCQ) constructed by W. Janke, G. Erdmann, K. W. Kallus, in the Polish language compilation by E. Januszewska, Buss-Durkee Hostility – Gild Inventory, developed in Polish by Choynowski. Results. Statistically significant differences were found in terms of self-image features, ways of coping with stress and activity displayed on the Internet between the youth who had and did not have a profile on the social networking site. Conclusions. Significantly more young people who have a profile on a social networking site share their personal data with strangers met through the Internet, use internet services and make purchases online, compared to the youth who do not have this profile. Young people with a profile on a social portal are characterized by greater timidity, difficulties in coping with stress and everyday tasks, less perseverance, entrepreneurship, effectiveness in the implementation of tasks, less self-confidence, less autonomy, responsibility and tolerance in comparison with young people who do not have a profile. Young people who have a social media profile are more likely to turn to other people in a stressful situation to request support and advice